A Study on the Impact of Crystalline Hydrophilic Additive and Microcapsules on Concrete Freeze-Thaw Durability - Gojević, Anita; Netinger Grubeša, Ivanka; Hadzima-Nyarko, Marijana (Civil Engineering Journal, 2025)
This paper evaluates the effectiveness of a crystalline hydrophilic additive and chemical microcapsules in enhancing concrete’s freeze-thaw resistance at both material and structural levels. Three concrete mixes were tested: a reference mix, one with the crystalline additive and one with microcapsules. Cubic specimens were tested for compressive strength, water absorption and relative dynamic modulus of elasticity before, after and during 56 freeze-thaw cycles (according to CEN/TR 15177). The reinforced concrete beams underwent the same freeze-thaw regime and were tested under displacement-controlled cyclic loading to evaluate residual capacity and serviceability. Although both additives improved freeze-thaw resistance, beams with the microcapsule performed better on most criteria, including increased stiffness (+14%), load-bearing capacity (up to +22%) and ductility after freeze-thaw loading. Notably, all mixes showed an unexpected increase in compressive strength after cycling. Although the microcapsules provided the best overall performance, the crystalline additive was more effective in reducing water absorption. The study highlights the practical applicability of microcapsules for structural elements and demonstrates their potential to improve performance properties under harsh environmental conditions. The research novelty lies in the dual-level evaluation – material and structural – and the systematic comparison of two innovative additives, allowing a more comprehensive understanding of their performance under freeze-thaw conditions.